ENGLISH TEACHERS’ ATTITUDES TOWARDS GOOGLE FORM AS AN ONLINE ASSESSMENT TOOL - Ramadhani, Fadhil; Sukyadi, Didi; Purnawarman, Pupung (Universitas PGRI Sumatera Barat, 2023)
The Covid-19 pandemic has resulted in a shift into online learning, including in English language learning. One of the popular online learning platforms in Indonesia is Ruangguru, where students can access English learning materials on its application anytime and anywhere. This study aims to find out Indonesian high-school students’ perceptions of Ruangguru as an English online learning tool. A questionnaire and guided interviews were used to collect the data from Indonesian high-schoolers who use Ruangguru. The data were analyzed using a mixed-methods approach using descriptive statistics and qualitative analysis. The results indicate that Ruangguru is positively perceived by online English learners, namely because its videos give clear instructions that can motivate the students into becoming autonomous learners. However, some learners still encounter problems regarding the constraints posed by online learning and digital gap. Regardless, most of them see Ruangguru as a helpful English learning tool during the online education era.